Associations Between Autism Symptomatology, Alexithymia, Trait Emotional Intelligence, and Adjustment to College - Davidson, Denise; Morales, Dakota (Frontiers in Psychology, 2022)
It has been asserted that the socio-emotional challenges associated with autism spectrum disorder (ASD) may be explained, in part, by the higher rates of alexithymia in individuals with autism. Alexithymia refers to difficulties in identifying one’s own emotional states and describing those states to others. Thus, one goal of the present study was to examine levels of alexithymia in relation to ASD symptomatology and trait emotion intelligence (EI). Trait EI is a multifaceted concept that captures emotional competencies and behavioral dispositions A second goal was to assess whether alexithymia, ASD symptomatology and trait EI served as significant predictors of adjustment to college, including academic, social, and personal-emotional adjustment. In addition to keeping with the spectrum nature of autism, this allowed us to capture those students who may not have received a formal diagnosis of ASD but report symptoms that can be indicative of ASD. This includes women, who are less likely to receive a diagnosis of ASD even when ASD symptomatology is present. The results of the study showed that students reporting higher levels of ASD symptomatology also reported significantly higher levels of alexithymia and lower trait emotional intelligence (trait EI) than those with less or no symptomatology. Alexithymia was also negatively related to trait EI, and both alexithymia and ASD symptomatology were found to be significant predictors of trait EI. However, only trait EI was a significant predictor of adjustment to college and only for social adjustment. These findings suggest that support programs that develop trait EI skills may improve the college experience for students with ASD, regardless of alexithymia or ASD symptomatology.